Adaptive Redundancy-Based Transmission for Wireless Sensor Networks - Ng, Jin Ren; Goh, Vik Tor; Yap, Timothy Tzen Vun; Shuib, Mustaffa Kamal (Faculty of Engineering, Universitas Indonesia, 2019)
Wireless Sensor Networks (WSNs) are built upon tens to thousands of sensor nodes dispersed across a geographical area. Most sensor nodes have limited on-board resources, such as limited computing capabilities and limited power. These issues can reduce the reliability of the sensor nodes, which, in turn, affects the robustness of the WSN as a whole. One of the components that can be affected is the data transmission system of the sensor nodes. We propose a reliable transport layer protocol that uses a combination of redundant packets and probabilistic transmission to ensure reliable transmission of data while maintaining the efficiency of the network. The proposed protocol does not require acknowledgement packets, such as the transmission control protocol (TCP) and yet its efficiency is similar to that of the user datagram protocol (UDP). In this paper, we explain the proposed protocol and demonstrate how it can achieve 7% improvements in reliability while maintaining 77% efficiency compared to UDP. © IJTech 2019.